(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article deals with foreign language information-educational environment: content, qualification demands and mechanisms of organization. In the condition of formation of intercultural communicative competence, foreign language is informational and educational environment, formed personality-oriented foreign-language electronic educational resources. Educational environment is a set of components of electronic educational resources, providing system integration tools of information and communication technologies in the educational process in order to improve its efficiency and acts as a means of building a student-centered educational system.